Analisis Perbandingan Putusan Hakim terhadap Utang Piutang sebagai Alasan Perceraian di Pengadilan Agama Kelas 1A Makassar - Muh. Mudassir; Arsyad, Azman (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2024)
The main problem in this research is related to the Comparative Analysis of Judges' Decisions on Debts and Receivables as a Reason for Divorce that occurred in the Makassar Class 1A Religious Court which aims to find out why Indonesian law does not make debts and receivables a basis for divorce, and to find out what factors are taken into consideration. the judge in granting a divorce case because of debts and receivables. The research method used by the author is qualitative research, which was carried out at the Class 1A Makassar Religious Court. Data sourced from cases 1) 2855/Pdt.G/2020/PA.Mks, 2) 1847/Pdt.G/2021/PA.Mks, and 2) 2847/Pdt.G/2021/PA.Mks, Judges, Figures Religion, Posbakum and Society. Field research techniques are research that is directly related to the research object being studied as well as Library Research, interviews and documentation. The data analysis processing is through deductive, inductive analysis and comparative methods. The results of this research are that the basis for the judge's consideration in deciding the Class 1A Makassar Religious Court decision case is by referring to the arguments of the lawsuit, evidence, and the statements of witnesses. The judge's considerations in granting the divorce petition filed by the husband against his wife were because they had debts for which no solution could be found for peace and harmony in their household. Meanwhile, according to Islamic law regarding the talak divorce case which the applicant submitted to the Makasar Religious Court on the grounds that the wife had a lot of debt, Islam views this divorce case as basically having no reason regarding debts and receivables, but because debts and receivables are the main reason husband and wife often experience problems. disputes and quarrels which cause there to be no longer a harmonious relationship and cannot be maintained, with that Islam views that this is a case of shiqaq (a sharp and continuous dispute between husband and wife) regarding responsibility for debts at the time of divorce, then debts arising from wrongdoing. one husband or wife cannot be transferred to that party without the knowledge or consent of the other party. In the absence of prior agreement from both parties, personal debts cannot be settled with the couple's personal assets or joint assets. So, in a situation like this, the party concerned will bear responsibility for the loan.